ТӘЖЕТДИН СЕЙТЖАНОВТЫҢ ПОЭМАЛАРЫНЫҢ КӨРКЕМЛИК ӨЗГЕШЕЛИКЛЕРИ - Сарсенбаева, А.К. (FAN va JAMIYAT, 2023)
The article analyzes the ideological, thematic and artistic features of such poems by the national poet of Karakalpakstan T. Seytzhanov as "The Tale of the Mother", "The Word of the Father", "Misguided Happiness", "Fate", which occupy a significant place in his work, and also draws conclusions by them.